Internet connectivity disruption in Oman (Oman) - Voidly (2026)
CRITICAL severity disruption detected in Oman. Confidence: 70%. Data sourced from IODA.
Network Disruption Incident ID: OM-2026-0059
Keywords: internet disruption; OM; disruption; critical